Morey, Chris (London, 2013)
2013 "Morey, Chris", 2013, HistoryTalk Chris was born in Somerset in 1947 and went to Reading University following the expansion of HE outlined in the Robbins report. He then started work for Ealing Council in 1969 as a trainee librarian. He attended Ealing technical College (now TVU) to obtain a post- graduate qualification in librarianship. His family had no explicit political background but his school years radicalised him as the 1960s was a period of change in ideas and attitudes. Describes changes to library service and the problems thrown up for staff and unions.